Progress of key strategies in development of electrospun scaffolds: bone tissue - Pramanik, Sumit; Pingguan-Murphy, Belinda; Abu Osman, Noor Azuan (2012)
There has been unprecedented development in tissue engineering (TE) over the last few years owing to its potential applications, particularly in bone reconstruction or regeneration. In this article, we illustrate several advantages and disadvantages of different approaches to the design of electrospun TE scaffolds. We also review the major benefits of electrospun fibers for three-dimensional scaffolds in hard connective TE applications and identify the key strategies that can improve the mechanical properties of scaffolds for bone TE applications. A few interesting results of recent investigations have been explained for future trends in TE scaffold research.